Sztuka jako jedna z form readaptacji społecznej skazanych na przykładzie programu „Ostatnia Mila” - Kotowska, Monika (Studia Prawnoustrojowe, 2019)
In the last 20 years the distinct intensification of research on the importance of artistic activities in prisons can be observed. It is stressed in literature that the results of artistic activities in penitentiaries have educational and therapeutic value. The article describeses „Last Mila” – the project carried out in Gębarzewo prison in 2015–2016. The „Last Mila”, by giving the prisoners opportunity to readaptation, establish a dialogue with people from the „outside” and contact with art, creates a chance to develop awareness, and so take a significant step on the path to personal freedom